Paying off populism: EU regional policy decreases populist support - Robert Gold; Jakob Lehr (Kiel Institute for the World Economy (IfW Kiel), 2024)
How to break the populist wave? With the elections to the European Parliament ahead, and the Presidential Elections in the US looming, this question bothers policymakers in many Western democracies. Our study shows that regional policies effectively decrease populist support. Specifically, EU Regional Policy investing into the development of lagging-behind regions decreases the vote share obtained by right-fringe populist parties by 15-20 percent. Moreover, regional policy investments increase trust in democratic institutions, and decreases discontent with the EU. – – Wie kann der Aufstieg des Populismus gestoppt werden? Angesichts der bevorstehenden Wahlen zum Europäischen Parlament und der Präsidentschaftswahlen in den USA beschäftigt diese Frage politische Entscheidungsträger in vielen westlichen Demokratien. Unsere Studie zeigt, dass regionalpolitische Maßnahmen die Unterstützung populistischer Parteien wirksam verringern können. Konkret finden wir, dass die EU-Regionalpolitik, die in die Entwicklung von rückständigen Regionen investiert, dazu führt, dass der Stimmenanteil rechtspopulistischer Parteien um 15-20% sinkt. Darüber hinaus erhöhen regionalpolitische Investitionen das Vertrauen in demokratische Institutionen und verringern die Unzufriedenheit mit der EU.
Keywords: 330; Populism; Regional Policies; European Integration; Regression Discontinuity Design; Populismus; Regionalpolitik; Europäische Integration; Regression Discontinu-ity Design